2004
DOI: 10.1111/j.1365-2516.2004.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of bleeding disorders: a report on the UK Haemophilia Centre Doctors’ Organisation annual scientific symposium, 10th October 2003

Abstract: The UK Haemophilia Centre Doctors' Organisation (UKHCDO) held its annual scientific symposium in October 2003, at the International Centre for Life, Newcastle-upon-Tyne. The educational day covered a range of topics relating to the genetics of bleeding disorders, including advances in genetics and gene therapy, antenatal diagnosis and counselling. We present the proceedings from the educational day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…21 Knowledge of the molecular basis of type 1 vWD is only beginning to evolve. 52,53 Even though the vWF gene had been identified, early linkage studies of families with type 1 vWD suggested weak 54 or inconsistent 55 linkage to the vWF locus; in addition, earlier studies demonstrated linkage to the vWF gene in only 41% of families, 56 even though comprehensive sequencing of the vWF gene yielded 112 candidate mutations for which structure function relationships were being defined. Moreover, selected patients with type 1 vWD were found to be heterozygous carriers of type 3 defect, 57 but not all such individuals have symptomatic bleeding.…”
Section: Genetic Background Of Vwfmentioning
confidence: 99%
“…21 Knowledge of the molecular basis of type 1 vWD is only beginning to evolve. 52,53 Even though the vWF gene had been identified, early linkage studies of families with type 1 vWD suggested weak 54 or inconsistent 55 linkage to the vWF locus; in addition, earlier studies demonstrated linkage to the vWF gene in only 41% of families, 56 even though comprehensive sequencing of the vWF gene yielded 112 candidate mutations for which structure function relationships were being defined. Moreover, selected patients with type 1 vWD were found to be heterozygous carriers of type 3 defect, 57 but not all such individuals have symptomatic bleeding.…”
Section: Genetic Background Of Vwfmentioning
confidence: 99%